04 Improving the prehospital identification and management of people presenting to the ambulance service with COVID 19 symptoms. Issue 9 (19th August 2021) - Fitzpatrick, David; Moore, Matthew; Best, Catherine; Andreis, Federico; Duncan, Edward; Esposito, Martin; Corfield, Alasdair; Dcobbie, Richard; Lowe, David
Abstract : Background: Little is known about how patients with COVID-19 present to ambulance services or their outcomes. Between 1st March and 31st August 2020 we investigated individuals who called the Scottish Ambulance Service (SAS) with COVID-19 symptoms and those that were later tested COVID-19 positive. We analysed i) their demographic and clinical characteristics; ii) their disposal; and iii) their admission and mortality outcomes. Methods: SAS and NHS Scotland Health Board data are routinely linked in a national database. These data evidence a patients journey from ambulance call to hospital attendance and subsequent outcome. Evidence of COVID-19 testing was identified 10 days either side of the call. Results: 171, 169 patients made 257, 207 calls during the study period. Of these, 2.8% (n=7, 305) were categorised as possible COVID-19 patients during telephone triage. From the flagged +ve patient calls 6% had a COVID-19 positive result, 29% had a negative COVID-19 result and the other 65% had no evidence of being tested. The majority (54%) were taken to the Emergency Department; 73% received further hospital care. The proportion of patient calls admitted within 10 days of the call was 31% for those not conveyed against 82% for conveyed. Final prehospital physiology for COVID-19 positive patients demonstrated lower oxygen saturations, higher respiratory rates and temperatures. 4.9% and 11.7% of patients conveyed to hospital died within 3 and 30 days vs 5.2% and 19.6% of patients not conveyed respectively. Conclusions: This study suggests telephone triage is not a reliable identifier of COVID-19 patients reinforcing existing requirements for Personal Protective Equipment. 30-day mortality rates differed between those patients initially conveyed vs not conveyed. Clinical characteristics of COVID-19 positive patients suggest they were clinically less well than other patients.